A Geocritical Reading of Daniel Defoe’s Moll Flanders - Dilek İnan (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
This study analyzes the rich spatial and platial references in Daniel Defoe’s picaresque novel Moll Flanders (1722) by using the prospect provided by the figure of the flâneur and geocritical criticism. The novel portrays a world of mobility and travel amongst places and Moll’s spatial experiences determine her survival and spiritual refinement. Theorists such as Edward Soja, Fredric Jameson and David Harvey have observed that place has a discursive/symbolic meaning beyond that of mere location. Spatial thinkers such as Henri Lefebvre, Michel Foucault, Yi-Fu Tuan, Marc Augé, and Edward Relph have defined a set of vocabulary related to space which will be helpful to explore the ways in which Defoe’s characters have depicted the human condition and its relation to space. While the notions of locality, displacement, mobility, and placelessness are explored in a setting of eighteenth-century chaos, the paper helps to further studies in Defoe studies especially in evaluating spatiality and lived experience.